Earthquakes, Volcanic Eruptions, and Other Geological Disasters During Historical Records In Yogyakarta Special Region, Indonesia - Mulyaningsih, Sri (Geological Agency, 2021)
DOI:10.17014/ijog.8.2.197-212Yogyakarta, Indonesia, is a very fast developing area. The Yogyakarta historical time is divided into PreOld Mataram Era (1st - 8th century), Old Mataram Era (8th - 12th century), and Young Mataram Era (since 16th century). Geology has recorded many intermittent natural disasters within those historical time: volcanism, earthquakes, and rock movements as well. Those natural disasters have caused lots of damages, shown by buried and collapsed old buildings. Larger volcanic eruptions were known to occur once in 50 - 150 years ago, which were mostly followed by lahars as far as 32 km from the crater of Merapi Volcano, of which the last eruption was in 2010. Earthquakes were identified based on bumpy foundations that particularly occurred in the first pile of temple stones, i.e. at the temples of Kedulan, Plaosan, Morangan, Gampingan, and Boko Palace. Surface fractures are also present on the base of the palace floors. During 18th - 21st century, larger earthquakes with magnitude of 5 - 8 Richter scale occurred once in 20 - 70 years, of which the last earthquake was in 2006. A geological study clarified that there was a marine volcanism during the Tertiary with radial normal faults. The normal faults have been potential to reactivate since Plio-Pleistocene untill now, shown by surface deformations at Sudimoro Hills with a mass movement occurence as happened in Imogiri (March, 17th 2019), Pleret (2018), Piyungan, and Dlingo (March, 17th - 18th 2019). A stratigraphic study of volcaniclastic deposits around Gendol, Opak, Kuning, and Bedog Rivers shows potential floods around the rivers.